WACANA PKI DAN KEKERASAN SIMBOLIK DALAM PROGRAM MISTER(I) TUKUL “EPISODE PEMBANTAIAN KEDIRI” - Kamil Alfi Arifin (Jurnal Dakwah Tabligh, 2018)
This article explores discourse of Indonesian’s Communis Party (PKI) in reality show program of Mister(i) Tukul (Pembantaian Kediri’s episode) and simbolic violence in its. This articles found that this program has reflected and repoduced discourse dominant of PKI. Thus, this program was regarded contain simbolic violence.